Gastrointestinal Stromal Tumor- An unusual presentation - Jha, Anamika; Paudel, Bigyan; Kasyap, Akhilesh (Nepalese Journal of Radiology, 2018)
Gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor of the gastrointestinal tract which earlier was classified as leiomyomas, leiomyosarcomas and leiomyoblastomas. These are known to have specific markers and are important to diagnose as targeted chemotherapy is available. Our case represents one of the ends of the spectrum of clinical presentation of gastrointestinal tumors – an aggressive large mass at a younger than the usual age of presentation. Though challenging, imaging diagnosis of GIST is very important as it can guide the confirmation of the same by identification of the markers on pathology.